SCHOOL BUDGET MANAGEMENT TRAINING AT SMP KATHOLIK DON BOSCO SEMBORO TANGGUL – JEMBER - Prayitno, Budi; Wany, Eva; Yustisie, Renta (Journal of Social Comunity Services, 2025)
Objective: This study aims to enhance financial and administrative management at SMP Katholik Don Bosco Semboro Jember, an educational institution that has experienced significant growth in assets and scale. This growth necessitates the adoption of efficient and accountable financial practices to establish robust and credible organizational governance. Method: The method employed includes a structured approach of training sessions, continuous assistance, and activity evaluations. Each session is designed to address gaps in financial and administrative management, focusing on budget discipline, financial planning, and accurate record-keeping. A training module was also provided to aid in participants' understanding of the material. Results: The activities were well-received by the school's finance and administrative staff, resulting in improvements in budget planning, transparent financial reporting, and streamlined administrative processes. Adherence to applicable financial standards further enhanced accountability and efficiency in the school's financial management. Novelty: The novelty of this study lies in its comprehensive, practice-oriented training model tailored specifically for educational institutions. This model offers a replicable framework for similar foundations seeking to strengthen their financial governance. The outputs include a training module and an improved financial management framework adapted to the needs of SMP Katholik Don Bosco Semboro Jember, providing long-term benefits for the foundation’s financial accountability and organizational credibility.